Analysis of Factors Affecting Labor Productivity in Fixing and Formwork Work on the Joglo Fly Over Rail Project - Azhari, Muhammad Khalid Hasyim; Amar, Tsulis I’qbal Khairul (ASTONJADRO, 2024)
The study investigates factors influencing worker productivity in construction projects, recognizing the challenge of balancing a sufficient workforce without compromising efficiency. Employing work sampling and regression analysis, eight variables are identified: experience, education, health, family dependents, wages, field conditions, weather, and K3. The results reveal that, collectively, these variables fall below established standards, indicating a lack of significant impact on labor productivity. Notably, experience emerges as the most influential factor, although its significance level remains below the threshold. Despite this, the variable’s calculated t value of 1.772 suggests its relative importance compared to others. The study underscores the need for meticulous labor selection, emphasizing experienced individuals to enhance overall productivity. While no single variable surpasses the significance threshold, the findings provide valuable insights for construction project management, urging a focus on experienced workers to improve productivity levels. Ultimately, the study contributes to understanding the nuanced dynamics of worker productivity in construction, urging practitioners to consider experience as a pivotal factor in their labor selection process.